2020
DOI: 10.21203/rs.3.rs-22032/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neoantigen polypeptide vaccines induce effective antitumor response in colorectal cancer

Abstract: Background: The role of neoantigens in cancer immunotherapy is crucial. However, the effectiveness and safety of personalized neoantigen vaccines in colorectal cancer (CRC), especially in Chinese population, has not been well studied. This paper mainly explores the feasibility and effectiveness of personalized neoantigen vaccines in CRC treatment. Methods: Whole-exome sequencing and transcriptome sequencing were used to identify somatic mutations, RNA expression and human leukocyte antigen (HLA) alleles. Neoan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…[38] For instance, TSHZ3-L523P, RARA-R83H, TP53-R248W, EYA2-V333I, and NRAS-G12D specific-patient neoantigens were predicted to induce NRT antitumor responses in CRC. [19] Although neoantigens are potential targets for personalized vaccines and NRT therapy, most neoantigen-targeted therapies are customized and costly. To overcome these limitations, "shared neoantigens" could be more suitable for patients.…”
Section: Neoantigensmentioning
confidence: 99%
See 2 more Smart Citations
“…[38] For instance, TSHZ3-L523P, RARA-R83H, TP53-R248W, EYA2-V333I, and NRAS-G12D specific-patient neoantigens were predicted to induce NRT antitumor responses in CRC. [19] Although neoantigens are potential targets for personalized vaccines and NRT therapy, most neoantigen-targeted therapies are customized and costly. To overcome these limitations, "shared neoantigens" could be more suitable for patients.…”
Section: Neoantigensmentioning
confidence: 99%
“…[9][10][11] Despite the increase in the survival of CRC patients through the implementation of screening programs and targeted therapy in recent decades, the relative five-year survival of CRC patients is still only ≈68%. [12] Evidence demonstrated that MSI-H CRC is associated with increased frequency of tumor-infiltrating lymphocytes (TILs) and high rates of tumor mutation, which justifies the use of various T cell-associated immunotherapies, such as using immune checkpoint inhibitors, neoantigen-reactive T cell (NRT) therapy and chimeric antigen receptor (CAR)-T cells in MSI-H CRC. [13] However, immunotherapy for CRC treatment still has a long way to go because immune checkpoint blockers' effectiveness and success rate have been very low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Active immunotherapy consists mainly of tumor vaccines against peptides, DNA, RNA, or dendritic and tumor cell types. [16][17][18][19][20] For patients who do not respond to other treatments for CC, tumor vaccines represent a promising treatment method. Two biomarkers, CCR8 and GUCY2C, were considered feasible as tumor vaccines in an animal trial, and a dendritic cell vaccine was shown to improve the prognosis of CC patients with surgically amenable liver metastases.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Combined with surgery, chemotherapy, or other treatment patterns, tumor vaccines can delay disease progression to a certain extent. [16][17][18][19][20][21][22] However, except for RNA vaccines, tumor vaccines have shown some fatal flaws. For example, peptide vaccines easily allow antigenic escape and have low immunogenicity, DNA vaccine integration into the host genome makes it ineffective, and dendritic cell vaccines have high resource costs.…”
Section: Introductionmentioning
confidence: 99%